Effects and Consequences of Zombie Lending - Petkova, Anika (Research Papers, 2021)
Zombie companies are defined as companies that are unable to service their debts for a long period of time. In this context, zombie lending is defined as financing of zombie companies under particularly favorable conditions in order to prevent bankruptcy, induce recovery of the company, incl. stimulating investment activity and employment. Numerous studies demonstrate that this type of companies worldwide fail to increase their productivity and efficiency and therefore use the allocated liquid funds in order to cover past debts, which proves that zombie lending, incl. and the extended government bond purchase programs used do not stimulate domestic investment and real economic growth rates. Aforementioned adverse effects related to the negative effects of zombie lending imply the implementation of targeted policies aimed at strict monitoring of companies and the application of unified standards and requirements for lending and providing liquidity support by financial institutions.